El Pensamiento Crítico Como Estrategia Didáctica Musical En La Educación Emancipatoria Del Alumno En Educación Primaria - Luis del Barrio Aranda (European Scientific Journal, ESJ, 2017)
Our report is concerned with the study of critical thought in musical education as a capacity which encourages the intellectual autonomy of students in primary education. After a theoretical review, based on the conceptualization and the description of the features that identify it, we provide a practical argument for its educational consideration with the development of a working with two groups of sixth grade of primary education, in which students adopt an active role becoming an element of reflection, analysis and construction of learning the musical activity. The conclusion of the study allows us to demonstrate that the promotion of reflective and critical thinking in a system of learning tasks, from cooperative work stimulates the natural development of the communication and autonomy as fundamental skills in metacognitive learning music.